Neurologic Care of COVID-19 in Children - Boronat, Susana (Frontiers in Neurology, 2021)
Most children with SARS-CoV-2 infection have relatively mild clinical symptoms without fever or pneumonia. Severe pediatric cases may rapidly progress to acute respiratory distress syndrome, septic shock, refractory metabolic acidosis, coagulation dysfunction and multiple-organ failure. This article will review 2 different aspects of neurological involvement related to this infection in children. In the first part I will review the neurological abnormalities reported in children caused by this viral infection. Symptoms such as anosmia, dysgeusia, headache, and muscle pain have been noted in adults, along with reports of central and peripheral nervous system involvement. COVID-19-related neurological symptoms seem infrequent in children, although some cases have been reported. In the second part, I will discuss how the COVID-19 pandemic has impacted in the health care system of some countries, causing collateral damage to general pediatric care and in particular to those children affected with chronic diseases, mainly neurological conditions, including cerebral palsy, neuromuscular disorders, autism, intellectual disability, attention deficit and hyperactivity disorder (ADHD), epilepsy or patients needing neurosurgical procedures.